2017
DOI: 10.1016/j.ijmedinf.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Remotely engaged: Lessons from remote monitoring in multiple sclerosis

Abstract: Objectives Evaluate web-based patient-reported outcome (wbPRO) collection in MS subjects in terms of feasibility, reliability, adherence, and subject-perceived benefits; and quantify the impact of MS-related symptoms on perceived well-being. Methods Thirty-one subjects with MS completed wbPROs targeting MS-related symptoms over six months using a customized web portal. Demographics and clinical outcomes were collected in person at baseline and six months. Results Approximately 87% of subjects completed wbP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…In Engelhard et al [9] some participants felt that questions were irrelevant to them, and did not want to continue reporting symptoms which showed no sign of change. Cultural relevance of study support materials was also reported to enhance engagement [25]; however, this was a qualitative study that provided no evidence of how it enhanced engagement.…”
Section: Convenience and Accessibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…In Engelhard et al [9] some participants felt that questions were irrelevant to them, and did not want to continue reporting symptoms which showed no sign of change. Cultural relevance of study support materials was also reported to enhance engagement [25]; however, this was a qualitative study that provided no evidence of how it enhanced engagement.…”
Section: Convenience and Accessibilitymentioning
confidence: 99%
“…Some studies reported that problems such as 'creating user accounts, answering intake question and navigating content due to unexpected behavior of keyboards, scroll bars, buttons, and other interface widgets' could be addressed with minor adjustments [22] although the authors provided no data on changes that had improved engagement. Engelhard et al [9] reported that where technical difficulties arose all could be solved by a phone call with the study coordinator, again the authors offered no data to back up this claim.…”
Section: Usabilitymentioning
confidence: 99%
See 3 more Smart Citations